Investigating the Usage of Medicinal Plants and Herbal Products in Aceh to Address COVID-19 Symptoms: A Cross-Sectional Survey - Suryawati, Suryawati; Rasydi, Ahmad; Puspita, Nanda Ayu; Hertiani, Triana (Malacca Pharmaceutics, 2023)
Medicinal plants have been used worldwide as supportive therapy in reducing symptoms of various diseases, including COVID-19 symptoms. The objective of this study was to investigate the use of medicinal plants and herbal products in respondents who experienced symptoms of COVID-19 in Aceh, Indonesia. A cross-sectional study was conducted, involving 384 respondents from the age group over 18 years old residing in Aceh Province, Indonesia. Data was collected via an online questionnaire consisting of 4 structured questions to assess the types and names of medicinal plants, the time of use, and the purpose of using medicinal plants. The results showed that nearly half of the study population (181 respondents) consumed medicinal plants and commercial products, mainly for the reason to enhance their immunity (49.7%), followed by to overcome the COVID-19 symptoms (26.7%). Amongst all medicinal remedies mentioned in this study, Ginger (Zingiber officinale) and turmeric (Curcuma longa) are the most widely used, which were consumed by 65.5% of medicinal plant and herbal products users. The other medicinal plant chosen by the study population were lemon (Citrus lemon), Java Ginger/temulawak (Curcuma zanthorrhiza), and Habbatus sauda (Nigella sativa). Although the majority of the respondents had used the herbal remedies prior contracting COVID-19 symptoms (45.5%), a third of the respondents consumed traditional medicine during the symptomatic period only (less than two weeks). This study has demonstrated the characteristics of the consumption of medicinal plants and their commercial products in Aceh, during the occurrence of COVID-19 symptoms in the study population.